An unusual glycerol-3-phosphate dehydrogenase in Sulfolobus acidocaldarius elucidates the diversity of glycerol metabolism across Archaea - Christian Schmerling; Carsten Schroeder; Xiaoxiao Zhou; Jan Bost; Bianca Waßmer; Sabrina Ninck; Tobias Busche; Lidia Montero; Farnusch Kaschani; Oliver J. Schmitz; Jörn Kalinowski; Markus Kaiser; et al. (Communications Biology)
Abstract Glycerol is highly abundant in natural ecosystems and serves as both an important carbon source for microorganisms as well as a promising feedstock for industrial applications. However, the pathways involved in glycerol degradation in Archaea remain unclear. Here, we show that the thermoacidophilic Crenarchaeon Sulfolobus acidocaldarius can grow with glycerol as its sole carbon source and characterize the mechanisms involved in glycerol utilization. We show that after uptake involving facilitated diffusion, glycerol is phosphorylated to glycerol-3-phosphate by glycerol kinase (GK), followed by oxidation to dihydroxyacetone phosphate catalyzed by an unusual glycerol-3-phosphate dehydrogenase (G3PDH) with a previously undescribed type of membrane anchoring via a CoxG-like protein. Furthermore, we show that while S. acidocaldarius has two paralogous GK/G3PDH copies (saci_1117-1119, saci_2031-2033) with similar biochemical activity, only saci_2031-2033 is highly upregulated and essential on glycerol, suggesting that distinct enzyme pairs may be regulated by different environmental conditions. Finally, we explore the diversity of glycerol metabolism enzymes across the Archaea domain, revealing a high versatility of G3PDHs with respect to interacting proteins, electron transfer mechanisms, and modes of membrane anchoring. Our findings help to elucidate the mechanisms involved in glycerol utilization in Archaea, highlighting unique evolutionary strategies that likely enabled adaptation to different lifestyles.